2007
DOI: 10.1152/ajpgi.00392.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal maternal separation of rat pups results in abnormal cholinergic regulation of epithelial permeability

Abstract: Gareau MG, Jury J, Perdue MH. Neonatal maternal separation of rat pups results in abnormal cholinergic regulation of epithelial permeability. Am J Physiol Gastrointest Liver Physiol 293: G198-G203, 2007. First published May 17, 2007; doi:10.1152/ajpgi.00392.2006.-Neonatal maternal separation (MS) predisposes adult rats to develop stressinduced mucosal barrier dysfunction/visceral hypersensitivity and rat pups to develop colonic epithelial dysfunction. Our aim was to examine if enhanced epithelial permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 44 publications
7
96
1
Order By: Relevance
“…79 Stress-induced enhancement of colonic permeability was mimicked by exogenous administration of CRF, 33 and abolished by pretreatment with the peripheral administration of the non-selective CRF antagonists astressin or -helical CRF 9-41 . 37,55,80 Likely, the selective CRF 1 receptor agonist, cortagine, 48 the selective CRF 1 receptor antagonist, SSR-125543, 80 and the selective CRF 2 receptor antagonist, antisauvagine-30, 78 reduced the response, supporting the participation of both CRF receptors in the modulation of colonic permeability.…”
Section: Permeabilitymentioning
confidence: 87%
See 1 more Smart Citation
“…79 Stress-induced enhancement of colonic permeability was mimicked by exogenous administration of CRF, 33 and abolished by pretreatment with the peripheral administration of the non-selective CRF antagonists astressin or -helical CRF 9-41 . 37,55,80 Likely, the selective CRF 1 receptor agonist, cortagine, 48 the selective CRF 1 receptor antagonist, SSR-125543, 80 and the selective CRF 2 receptor antagonist, antisauvagine-30, 78 reduced the response, supporting the participation of both CRF receptors in the modulation of colonic permeability.…”
Section: Permeabilitymentioning
confidence: 87%
“…23 This increase was glucocorticoid-mediated because adrenalectomy and pharmacologic blockade of glucocorticoid receptors inhibited the response, and dexamethasone increased gastrointestinal permeability in control rats. 23 Similarly, rats models of chronic stress (maternal deprivation, 55,[77][78][79] WAS, 45 and crowding stress 52 ) also show increased ionic permeability, and macromolecular permeability throughout the intestine. The increase was mediated partly by mechanisms including, muscarinic and nicotinic pathways, activation and number of mast cells and the release of nerve growth factor.…”
Section: Permeabilitymentioning
confidence: 99%
“…Stress induced in early life by neonatal maternal separation may affect colonic permeability and motility Coutinho et al, 2002;Gareau et al, 2007). When this condition is mimicked in a rat model of IBS, colonic smooth muscle contraction amplitude is increased and this is associated with an increased expression of L-type calcium ion channels in colonic smooth muscle, as the level of calcium in smooth muscle cells increased in response to Ltype calcium ion channel activation .…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…They also showed in following experiments that the levels of brain-derived nerve factor (BDNF), norepinephrine and 5-5-hydroxytryptamine (5-HT) in the cortex and hippocampus were significantly lower in GF mice than in SPF mice [188]. Improvements of stress-related symptoms by probiotic administration also support the possible regulatory effects of microbiota on HPA axis and brain functions [44,189]. Gareau et al [44] reported that probiotic treatments improved colonic dysfunction and corrected the higher corticosterone levels in stressed rats induced by maternal seperation.…”
Section: Intestinal Microbiotamentioning
confidence: 89%
“…Early life stress models such as maternal deprivation of pups from the dams have also been widely used [31,41,43,44], because stressful events in the early period of life (in the form of abuse, neglect or loss of the primary caregiver) have been shown to modify adult immune and gastrointestinal tract functions [12].…”
Section: Stress Models For Gastrointestinal Studiesmentioning
confidence: 99%